The Effect Of Psychological Factors Towards Purchasing Decisions Product Of Rumah Mode - WIGATI, Niki Galih, Drs. Wiyadi, MM., Ph.D (2015)
In global marketing now that many consumers visit a social network online community to gain apparel shopping informationand psychological factors involves in the stages of consumer decision making, the purpose of this study was to analyze the effect of psychological factors at social network online communities and provide an implication towards purchasing decision. The title of this research is The Effect of Psychological Factors Towards Purchasing Decisions. The purpose of this research is to analyze the effect of Psychological factors (Consciousness, Experience, Moral Responsibility and Shared Culture) towards purchasing decision by the member of online shopping "Rumah Mode" to buy their product. 150 respondents in this research are the member of online shopping "Rumah Mode". Technique sampling of research used was JUDGEMENT because researchers directly involved as members in the Group of Online shopping. This analysis results that Psychological factors (Consciousness, Experience, Moral Responsibility and Shared Culture) were Significant and Valid towards Purchasing Decision.